A (re)criação do Rio de Janeiro na telenovela lado a lado: a ficção como representação de uma cidade em transformação - Nóbrega Filho, Eduardo de Oliveira (2015)
This research’s thematic field is the Period Soap Opera with a look at the scenographical or recreated city, aiming to work with audio-visual tools and its possibilities of contribution to the city’s history. Therefore, Lado a Lado was elected the research's subject , written by João Ximenes Braga and Cláudia Lage, screened in 2012 - 2013 on Globo Television Network, whose historical construct of Rio de Janeiro at the beggining of the 20th century fits the melodrama. From this viewpoint, it is understood that although the soap opera Lado a Lado is a fictional work freely, inspired in specific historical events on that period, represents in a fictional fashion, the city of Rio de Janeiro during the urban process of modernization and social transformation. Together with the comprehension of language representation in an addressed space in and an specific time, utilized magnetic means to appropriate from the real city's historical construct, read and redefined by a different language: the soap opera. It is going to be questioned the way the soap opera appropriated from such historical context, recreating the heading towards modernity image of the city, which can also be seen as a mean of delivering information about the country's history to the general population.